Sinkronisasi Penggunaan Lahan dan Pola Ruang (Studi Kasus: Kabupaten Simeulue) - Fazlina, Yulia Dewi; Rusdi, Muhammad; M, Nurul Husna.; Karim, Abubakar; Manfarizah, Manfarizah; Arabia, Teti (Department of Agricultural Engineering, Syiah Kuala University, 2024)
Abstrak.Perubahan penggunaan lahan adalah proses perubahan dari penggunaan lahan sebelumnya menjadi penggunaan lahan lain yang bersifat permanen maupun sementara. Kabupaten Simeulue telah menetapkan Qanun Nomor 2 Tahun 2014 tentang Rencana Tata Ruang Wilayah Kabupaten Simeulue Tahun 2014-2034. Penggunaan lahan harus memperhatikan arahan pemanfaatan lahan yang tertuang dalam pola ruang. Sinkronisasi atau keselarasan penggunaan lahan dengan pola ruang yang telah ditetapkan dalam dokumen RTRW perlu dilakukan agar tidak terjadi penyimpangan/ketidakselarasan pada penggunaan lahan. Analisis keselarasan penggunaan lahan menggunakan geoprocessing, dengan menggunakan data shapefile penggunaan lahan Tahun 2021, dan data shapefile pola ruang Tahun 2014-2034. Kelas keselarasan dibagi menjadi tiga kelas, yaitu selaras, tidak selaras, dan transisi/belum selaras. Luas Penggunaan lahan yang selaras dengan pola ruang seluas 152.808,65 Ha (71,91%), sedangkan luas penggunaan lahan yang tidak selaras dengan pola ruang seluas 13.054,01 Ha (6,14%), dan penggunaan lahan yang belum selaras atau transisi seluas 46.649,34 Ha (21,95%).Land Use Synchronization and Spatial Patterns (Case Study: Simeulue District)Abstract.Land use change is the process of changing from previous land uses to other land uses that are permanent or temporary. Simeulue Regency has established Qanun Number 2 of 2014 concerning the Regional Spatial Plan of Simeulue Regency for 2014-2034. Land use must pay attention to land use directions contained in spatial patterns. Synchronization or alignment of land use with spatial patterns that have been determined in the RTRW document needs to be done so that there are no deviations / misalignments in land use. Land use alignment analysis using geoprocessing, using land use shapefile data for 2021, and spatial pattern shapefile data for 2014-2034. The alignment class is divided into three classes, namely aligned, misaligned, and transitional/unaligned. Land use area that is in harmony with spatial patterns is 152,808.65 Ha (71.91%), while land use area that is not in harmony with spatial patterns is 13,054.01 Ha (6.14%), and land use that is not aligned or transitional is 46,649.34 Ha (21.95%).